Beyond the Salary: Effects of Compensation, Non-Physical Work Environment, and Job Satisfaction at Universitas Majalengka - Nita Hernita; Farhan Muhamad Kamil Danopa (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aimed to investigate the effects of compensation, non-physical work environment, and job satisfaction on employee retention among educators. By analyzing these variables, this study seeks to identify the main factors that encourage administrative staff in higher education to remain committed to their institutions. Research Methodology: This study used a quantitative approach with a case study design. Data were collected using structured questionnaires distributed to the educators at Majalengka University. The sampling technique used was saturated sampling, data were analyzed using multiple linear regression to determine the direct effect of independent variables on employee retention Results: The findings indicate that compensation does not significantly affect employee retention (? = ?0.055; p = 0.438). Conversely, the non-physical work environment (? = 0.204; p = 0.012) and job satisfaction (? = 0.302; p < 0.001) had significant positive effects on employee retention. The model explains 61.6% of the variance in employee retention (R² = 0.616), indicating a strong explanatory power. Conclusions: The study concludes that non-financial factors, particularly the psychological work environment and job satisfaction, play a more dominant role than compensation in retaining educational personnel in higher-education institutions. Limitations: This study is limited to a single university context and uses cross-sectional data, which may restrict generalization and causal interpretations. Contributions: This study contributes to the human resource management literature by providing empirical evidence of the importance of psychosocial workplace factors in strengthening employee retention strategies in higher education institutions.